Community-Based Tourism in Indonesia: A Bibliometric Analysis Using Scopus Database - Teuku Fahmi; Astiwi Inayah; Yulianto (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This study aims to map the research on community-based tourism (CBT) topics in Indonesia through bibliometric analysis using the Scopus database. Bibliometric analysis was conducted on 85 CBT-related publications in Indonesia to identify research trends, key topics, and collaboration networks. The results of the bibliometric analysis were then visualized using VOSviewer software. The study results show an increase in interest in CBT research in Indonesia, with a focus on the development of local communities that prioritize social and cultural aspects. Referring to the results of keyword co-occurrence analysis, the main topics that stand out in CBT research in Indonesia include community development, ecotourism, local community, local wisdom, and sustainable tourism. The collaboration network of Indonesian researchers seems to be firmly established with researchers from Australia, Malaysia, and Japan. Moreover, the results of the bibliometric analysis also confirm that the development of CBT has considerable potential in efforts to develop sustainable tourism in Indonesia. However, research related to identifying challenges and opportunities in the development of CBT in Indonesia is still needed. Ultimately, the bibliometric analysis that has been carried out contributes to a comprehensive understanding of CBT development studies in Indonesia.